A Framework Proposal for Analysis of Urbanization Policy - Erkan, Nihal Ekin (European Scientific Journal, ESJ, 2017)
This paper suggests a framework proposal for the analysis of urbanization policy as a public policy. Firstly, how urbanization policy is conceptualised is discussed. After, a framework for analysis of urbanization policy is suggested. Main elements of this framework are specified as (1) conditions that constitute urbanization policy background; urbanization logic produced by socio-economic structure; (2) political and administrative agents and other related actors and also their relations; forms of theoretically doing politics of actors; (3) key issue of urbanization policy and its prominent characteristics; process of urbanization policy; (4) change pattern of the policy. Paper ends up with an emphasis on an important inclusionary analysis for the development on urbanization policy making.